Działalność Koła PPR przy Głównym Urzędzie Cenzury MBP 1945–1947 - Charczuk, Wiesław (Komunizm: System - Ludzie - Dokumentacja, 2012)
The minutes of the meetings of the PPR Club (Polish Workers’ Party Club) of The MBP (The Ministry of Public Security) are an extremely valuable source of information about the way the party worked and the lives of the main members, who had created the whole structure of the GUC (Main Office of Censorship) that was the unit of the MBP between 1945 and 1947. A great attention was focused on the culture and education commission, which was supposed to be a an important unit of the MBP workers’ indoctrination. The way the commission worked was considered insufficient because the administration often changed their directives, that leaded to loss of discipline of the rank and file members of the party’s units. The existing documentation shows that the given commands were not often rethought. Even the members of the unit have no idea what the meeting was going to be about. There was no information about what was on the agenda. It was the reason why the members were unwilling to come to the meetings. According to the opinion of the employees and the party members, the meetings were considered boring, and the speakers were thought to be badly prepared to present their papers, and often did not have the slightest notion what was discussed. The analysis of the minutes shows the picture of a totalitarian country, units of which try to control all the possible areas of Poles’ lives, trying to accomplish the process of sovietization of Poland.